2020
DOI: 10.1002/er.5052
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of electrolyte flow management to increase the performance of Zn–air fuel cells

Abstract: Summary Zinc (Zn)–air fuel cells (ZAFCs) are one of the potential alternatives to fossil fuels. Because a flowing electrolyte can directly affect cell performance, we focused on the electrolyte management of a ZAFC. The ZAFC galvanostatic discharge was examined to determine its performance. The electrolyte concentration, temperature, and circulation rate were used as the operating parameters for discharge tests, and the relationship between electrolyte and cell performance was discussed based on the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, DHPS exhibited a considerably higher Complementary Operation Parameter Optimization. Other than developing new cell configurations, the operation parameters, such as the electrolyte flow rate and charging protocols, also have a profound influence on battery performance but often are complementary to a specific cell configuration, such as primary ZAFC, 126,127 charge−discharge-decoupled ZAFB, 115 and slurry-type ZAFB with a cylindrical 116,118 or planar module. 117,128 Despite the diverse cell configurations, there are still some common understandings.…”
Section: ■ Reaction Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DHPS exhibited a considerably higher Complementary Operation Parameter Optimization. Other than developing new cell configurations, the operation parameters, such as the electrolyte flow rate and charging protocols, also have a profound influence on battery performance but often are complementary to a specific cell configuration, such as primary ZAFC, 126,127 charge−discharge-decoupled ZAFB, 115 and slurry-type ZAFB with a cylindrical 116,118 or planar module. 117,128 Despite the diverse cell configurations, there are still some common understandings.…”
Section: ■ Reaction Engineeringmentioning
confidence: 99%
“…128 However, Yang et al also showed that after increasing the flow rate to a critical value, the performance enhancement became less profound than within a moderate range of flow rates. 127 With regard to the reverse process, namely, Zn electrodeposition, Khezri et al applied in situ optical imaging, ex situ microscopic imaging, and multiphysics simulation, revealing both the individual and combined effects of current density and flow rate. 118 Overall, increasing the flow rate and maintaining a moderate current density are essential to steer the ZnO:Zn ratio to minimal so that uniform Zn electrodeposition could be realized.…”
Section: ■ Reaction Engineeringmentioning
confidence: 99%
“…[24,39] In addition to the importance of using an alkaline electrolyte, it is also necessary to choose the right concentration: increasing the concentration of KOH can reduce the resistance of the electrolyte, but too high concentration can lead to increased viscosity [24] and cause faster consumption of the zinc anode. [40] According to the conclusions reached by Thomas et al [41] and by Sangeetha et al, [32] in this experimental setup it was chosen a KOH concentration of 40 wt%.…”
Section: Electrolytementioning
confidence: 99%
“…In addition, computational fluid dynamics (CFD) simulation has become a powerful tool in numerous prominent engineering fields and disciplines, which helps to predict complex phenomena based on the mathematical model. Thus, the CFD model consists of several governing equations such as the continuity equation, momentum equation, and Fick's diffusion law have been introduced to evaluate the performance in flowing-type ZAFC [14]. The oxygen distribution at a different inlet flow rate of electrolyte to find the optimum value was, therefore, predicted.…”
Section: Introductionmentioning
confidence: 99%